2021
DOI: 10.1007/s10055-021-00526-1
|View full text |Cite
|
Sign up to set email alerts
|

The ObReco-360°: a new ecological tool to memory assessment using 360° immersive technology

Abstract: One important feature of a neuropsychological test is its ecological validity, which defines how much patients’ test scores are linked to real-life functioning. However, many of the currently available neuropsychological tools show low to moderate levels of ecological validity. Virtual reality (VR) emerged as a possible solution that might enhance the ecological value of standard paper-and-pencil tests, thanks to the possibility of simulating realistic environments and situations where patients can behave as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…The photorealism of 360° environments may have elicited a visual memory encoding similar to that seen in everyday life, resulting in the greater visual encoding of stimuli, easier recall of items, and increased ecological validity of the evaluation technique. Overall, these results are consistent with those found by Pieri et al, which used a minor number of target objects to be remembered ( Pieri et al, 2021 ). For what concerns the recognition performance, the pattern of results is inverted: participants showed high levels of accuracy in both conditions but performed significantly better in the RBMT-III condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The photorealism of 360° environments may have elicited a visual memory encoding similar to that seen in everyday life, resulting in the greater visual encoding of stimuli, easier recall of items, and increased ecological validity of the evaluation technique. Overall, these results are consistent with those found by Pieri et al, which used a minor number of target objects to be remembered ( Pieri et al, 2021 ). For what concerns the recognition performance, the pattern of results is inverted: participants showed high levels of accuracy in both conditions but performed significantly better in the RBMT-III condition.…”
Section: Discussionsupporting
confidence: 92%
“…The present study aims to test a 360° technology for memory assessment compared to a traditional paper and pencil test included in the RBMT-III ( Wilson et al, 2008 ; Beschin and Urbano, 2013 ). Based on promising results from an earlier pilot study showing the feasibility of a 360° memory assessment ( Pieri et al, 2021 ), we improved technology using higher-level equipment to design ObReco-2 (Object Recognition version 2). Firstly, we present the results of a usability study (Study 1), and then the results of the clinical efficacy along with updated usability data (Study 2).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that virtual environments with 360°video are more photorealistic compared to 3D VEs and are also easier to implement, not requiring any special programming skills. Few works in literature have already showed that 360°VEs can provide a more ecological assessment of executive functions [13] and memory [12] . However, these approaches lacked of an integrated system that collects measures of cognitive functioning, such as those related to the patient's behaviour in the simulated scenario.…”
Section: State Of the Artmentioning
confidence: 99%
“…Being a preliminary study, the testing was focused on obtaining results that could be evaluated and collected in a short time. Then SUS was chosen considering the limited number of items compared to other evaluating methods and the evidence supporting its use in assessing VR systems [15] [11] [5] [12].…”
Section: Variables and Metricsmentioning
confidence: 99%
“…On the other hand, however, this reduced the potentialities offered by VR of deploying realistic environments (Minderer et al 2016;Parsons 2015). Up to date, the potential of recreating ecologically valid environments has been discussed mostly in the field of cognitive and neuropsychological interventions (Pieri et al 2021). In such a field, in fact, it is sometimes difficult to assess the patient's capabilities in ADLs by performing standard paper-and-pencil tests (Câmara et al 2021).…”
Section: Related Workmentioning
confidence: 99%